2015
DOI: 10.1002/prp2.110
|View full text |Cite
|
Sign up to set email alerts
|

Jadomycin breast cancer cytotoxicity is mediated by a copper‐dependent, reactive oxygen species–inducing mechanism

Abstract: Jadomycins are natural products biosynthesized by the bacteria Streptomyces venezuelae which kill drug-sensitive and multidrug-resistant breast cancer cells in culture. Currently, the mechanisms of jadomycin cytotoxicity are poorly understood; however, reactive oxygen species (ROS)–induced DNA cleavage is suggested based on bacterial plasmid DNA cleavage studies. The objective of this study was to determine if and how ROS contribute to jadomycin cytotoxicity in drug-sensitive MCF7 (MCF7-CON) and taxol-resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(59 citation statements)
references
References 49 publications
(119 reference statements)
1
58
0
Order By: Relevance
“…In the present study, flow cytometry showed that juglone increased the levels of ROS in MCF-7 cells, in agreement with previous findings (Inbaraj and Chignell, 2004), but that this effect was reduced in the presence of NAC. Increased ROS levels likely interfere with the functioning of the mitochondrial electron transport chain, and decrease mitochondrial transmembrane potential by reducing the oxidation state of the mitochondrial inner membrane and by damaging mitochondrial DNA and several key proteins (Hall et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, flow cytometry showed that juglone increased the levels of ROS in MCF-7 cells, in agreement with previous findings (Inbaraj and Chignell, 2004), but that this effect was reduced in the presence of NAC. Increased ROS levels likely interfere with the functioning of the mitochondrial electron transport chain, and decrease mitochondrial transmembrane potential by reducing the oxidation state of the mitochondrial inner membrane and by damaging mitochondrial DNA and several key proteins (Hall et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…After treatment the cells were washed 3 times with PBS and the DCF fluorescenceintensity was measure under the fluorescence microscope [24].…”
Section: Ros Measurementsmentioning
confidence: 99%
“…At the time of publication, over forty-five of the described jadomycins have been evaluated for biological activity, including various cancer cytotoxicity assays [7][8][9][10]13,15,[17][18][19][20]25,[32][33][34][35] and antimicrobial panels. 6,20,33,34 Jadomycins have been implicated in the inhibition of aurora kinase B 10,54 and topoisomerases.…”
Section: Looking Forwardmentioning
confidence: 99%
“…2,3 The jadomycins are distinct from the other natural product angucyclines by their inclusion of a nitrogenous heterocycle, 1 which is the result of a non-enzymatic incorporation of an amino acid into the polyaromatic core. 4,5 This non-enzymatic process has permitted the generation of a large library of jadomycins, enabling the determination of structureactivity relationships with respect to the antibiotic 6 and cytotoxic [7][8][9][10] activity of the jadomycins. Jadomycin nomenclature often includes the incorporated amino acid, for instance, jadomycin S (Jd S) refers to the natural product isolated through incorporation of L-serine into the jadomycin.…”
Section: Introductionmentioning
confidence: 99%